Water and Society 2013
DOI: 10.2495/ws130061
|View full text |Cite
|
Sign up to set email alerts
|

Integrating mobile bed numerical modelling into reservoir planning operations: the case study of the hydroelectric plant in Isola Serafini (Italy)

Abstract: This work aims at integrating the understanding of the river geomorphic dynamic into planning of reservoir operation rules. The case study is a 112 km long reach of the Po river in Italy, from Piacenza to Boretto. The Isola Serafini (IS) gate serves a large run-of-the-river hydroelectricity plant since 1962. The dam blocks a relevant amount of sediments and is cause, together with intense sand mining, for the river bed incision immediately downstream that has made several navigation and irrigation devices unus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…This reach has been significantly affected by riverbed degradation in the past and has a strategic role for navigation and flood defense. Our choice is also supported by the findings of Bernardi et al [2013], which have shown that this reach is the most sensitive to IS operation. Toward this aim, we refer to a complete historical time series of water inflows from 1964 to 1973 recorded at Piacenza, and at the relevant tributaries.…”
Section: The Case Study: the River Po And The Isola Serafini Hp Plantsupporting
confidence: 53%
See 3 more Smart Citations
“…This reach has been significantly affected by riverbed degradation in the past and has a strategic role for navigation and flood defense. Our choice is also supported by the findings of Bernardi et al [2013], which have shown that this reach is the most sensitive to IS operation. Toward this aim, we refer to a complete historical time series of water inflows from 1964 to 1973 recorded at Piacenza, and at the relevant tributaries.…”
Section: The Case Study: the River Po And The Isola Serafini Hp Plantsupporting
confidence: 53%
“…Our choice is also supported by the findings of Bernardi et al . [], which have shown that this reach is the most sensitive to IS operation. Toward this aim, we refer to a complete historical time series of water inflows from 1964 to 1973 recorded at Piacenza, and at the relevant tributaries.…”
Section: The Case Study: the River Po And The Isola Serafini Hp Plantmentioning
confidence: 99%
See 2 more Smart Citations
“…The physical constraints for the variables are given by the MEF in the meander, the minimum and maximum flow through the turbines and the safety limit against flood risk. Starting from the business as usual (BAU) simulation, representing the normal hydropower functioning, many different alternative operating rules have been run (Bernardi et al 2013) to analyse the sensitivity of the system to the management of the hydropower plant. The results showed the feasibility of the model to represent geomorphodynamic river processes in the presence of a stationary riparian vegetation condition.…”
Section: Model Application: the Case Of The Po River (Italy)mentioning
confidence: 99%